The Creation of Mandible Geometrical Model by Application of Synthetic Intellect Method - Karim Najm. Husain (Genius Journals, 2022)
Applying custom implants to treat bone fractures for each patient is the best treatment currently, and it represents the contemporary medical trend in the field of treating human bone fractures(Mandible). In order to design custom implants, we must provide a 3D barometric model that is compatible with a specific patient. The model of points is applied by utilizing a method of anatomical entities that form polygonal shapes and multiple regression to create a standard three-dimensional model of the mandible bone. For the purpose of obtaining good accuracy in predicting the parameters, mathematical calculations are formed for the parameters that represent the dimensions that can be obtained from medical images (CT,MRI ) and the anatomical trends that are taken from the coordinates of the measured points and the implementation of the synthetic intelligence method in the approach of creating a three-dimensional model of the mandible bone, as well as applying the analysis of The deviation to know and determine the geometric accuracy of the barometric model that has been worked on, and the result of analysis which performed between the resulting model and the initial model was satisfactory, which was done through the use of CAD and CATIA software
Keywords: Custom Implants; Anatomical Entities; Geometric; Model